ORIENTASI MASA DEPAN DITINJAU DARI SELF EFFICACY PADA SISWA SMA SANTO THOMAS 3 MEDAN: Orientasi masa depan, self efficacy - Immanuel Hutabarat (unprimdn.ac.id, 2019)
His study aims to find out relationship between self-efficacy and future orientation. The hypothesis of this study stated that there is a positive relationship between self-efficacy and future orientation, with the assumption that the higher self-efficacy of the student’s, the higher future orientation of the student’s and conversely the lower self-efficacy that students have, the lower future orientation of the student’s. The subjects of the study are 145 high school students at Santo Thomas-3 Medan selected by purposive sampling method. Data were obtained from a scale to measure self-efficacy and future orientation. Calculations were performed to test the requirement analysis (assumption), which consists of normality distribution test and linearity test for relationships. Data were analyses by using Product Moment with SPPS 17 for Windows. The results of data analysis showed a correlation coefficient of 0.718 (p < 0.05). This means that there is a positive relationship between self-efficacy and future orientation. The results showed that the contribution of a given variable of self-efficacy on future orientation wa 51,5 percent, while the remaining 48,5 percent was affected by other factors that not examined. Based on the results, it can be concluded that it means the hypothesis there is a positive relationship between self-efficacy and future orientation, is acceptable.